The liberalisation of China foreign trade policy in the framework of the WTO - Puślecki, Zdzisław W. (Economics of the 21st Century, 2016)
In this research work, the author focuses on the analysis of the liberalisation of foreign trade policy of emerging China in the world economy. What indicates the importance and innovativeness of the research is the presentation of the technical progress in P.R.China and the benefits resulting from the liberalised Chinese foreign trade policy. In accordance with the foreign trade policy theory further trade liberalisation and improved framework policies would increase trade and promote growth. It must be emphasized that openess to trade is associated with higher incomes and growth and there is a need for new approaches to trade cooperation in the light of the forces that are currently re-shaping international business. The key of trade developments within the broader socio-economic context is especially the rise of global supply chains, the general shift of trade power away from the West towards Asia. The main aim of the article is the presentation the liberalisation of foreign trade policy of emerging China in the world economy
Ekonomia XXI Wieku = Economics of the 21st Century, 2016, Nr 1 (9), s. 9-39
Keywords: emerging China; foreign trade policy; liberalisation effect; natural environment protection; bilateral agreements; world economy; wschodzące Chiny; zagraniczna polityka handlowa; efekt liberalizacyjny; ochrona środowiska naturalnego; porozumienia bilateralne; gospodarka światowa